The Influence of Information Sharing Behaviour on the Spread of Fake News about the 2024 Election on Social Media X - Arum, Yumna Nahdah; Wibowo, Kunto Adi (UMSU, 2024)
The influence of information dissemination behavior on the spread of fake news regarding the 2024 Election on Social Media X is a crucial focal point in the context of political and social dynamics. A comprehensive analysis reveals the complexity of the impacts of this behavior. Firstly, the dissemination of information on social media accelerates and broadens the spread of fake news, threatening the integrity of the electoral process. Secondly, the formation of filter bubbles and echo chambers can reinforce opinion polarization and limit the diversity of perspectives within society. Thirdly, this behavior can affect voter participation and create social instability. The importance of collective efforts to mitigate these negative impacts is evident through recommendations for enhancing digital literacy, enforcing strict regulations on fake news dissemination, and promoting transparency on social media. In conclusion, information dissemination behavior has profound implications for society, demanding serious attention to safeguard democracy and maintain social harmony.